Ion Beams in Nanoscience and Technology - Hellborg, Ragnar; Whitlow, Harry J.; Zhang, Yanwen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Energetic ion beam irradiation is the basis of a wide plethora of powerful research- and fabrication-techniques for materials characterisation and processing on a nanometre scale. Materials with tailored optical, magnetic and electrical properties can be fabricated by synthesis of nanocrystals by ion implanation, focused ion beams can be used to machine away and deposit material on a scale of nanometres and the scattering of energetic ions is a unique and quantitative tool for process development in high speed electronics and 3-D nanostructures with extreme aspect radios for tissue engineering and nano-fluidics lab-on-a-chip may be machined using proton beams. This book will benefit practitioners, researchers and graduate students working in the field of ion beams and application and more generally everyone concerned with the broad field of nanoscience and technology.
Trends in nanoscience and technology -- Nanoscale Engineering in the Biosciences -- High Speed Electronics -- Surface Modification Using Reactive Landing of Mass-Selected Ions -- Basic ion-matter interactions in nanometre scale materials -- Basics of Ion Scattering in Nanoscale Materials -- Box 1: Stopping of Ions in Nanomaterials -- Box 2: Sputtering -- Box 3: Ion Ranges -- Computer Simulation Methods for Defect Configurations and Nanoscale Structures -- Characterising Nanoscale Crystal Perfection by Crystal Mapping -- Box 4: Interatomic Potential -- Ion beam characterisation of nanoscale materials -- Medium Energy Ion Scattering for Near Surface Structure and Depth Profiling -- Box 5: Surface Crystallography Terminology -- Thin Film Characterisation Using MeV Ion Beams -- Nanoscale Materials Defect Characterisation -- Box 6: Nanoscale Defects -- Box 7: Diagnostic Ion Beam Luminescence -- Nanomaterials Science with Radioactive Ion Beams -- Nanoscale materials processing with ion beams -- Nanocluster and Nanovoid Formation by Ion Implantation -- Plasma Etching and Integration with Nanoprocessing -- Focused Ion Beam Machining and Deposition -- Box 8: Sample Preparation for Transmission Electron Microscopy Using a Focused Ion Beam -- Box 9: Integrated Circuit Chip Modification Using Focused Ion Beams -- Proton Beam Writing: A New 3D Nanolithographic Technique -- Box 10: Proton Beam Writing of Optical Structures -- Box 11: Tissue Engineering and Bioscience Methods Using Proton Beam Writing -- Box 12: Stamps for Nanoimprint Lithography -- Box 13: Silicon Micro/Nano-Fabrication Using Proton Beam Writing and Electrochemical Etching -- Nanoscale Materials Modification for Device Applications -- Luminescence, Ion Implantation, and Nanoparticles -- Micro- and Nanoengineering with Ion Tracks -- Equipment and practice -- Ion Accelerators for Nanoscience -- Focusing keV and MeV Ion Beams -- Ion Spectrometers and Detectors -- Electronics for Application of Ion Beams in Nanoscience.
Keywords: Materials; Particle acceleration; Nanotechnology; Material Science; Nanotechnology; Measurement Science and Instrumentation; Particle Acceleration and Detection, Beam Physics; Solid State Physics; Spectroscopy and Microscopy